Påverkas arbetsuppgifter för maskinpersonal av LNG-drift? Samt vilken behörighet krävs? - Hedman, Nina; Sjöqvist, Erik (My University, 2015)
This study investigates competence demands and education for engine room personnel onboard vessels powered by LNG. The study analyses how the routines are altered in comparison with traditional diesel-powered vessels. Furthermore, the study looks into how ship-owners and universities in Sweden are preparing themselves for the upcoming training requirements on engine room personnel. The result indicates that at the present date there are Interim Guidelines issued by IMO describing training and certification in two different groups, basic and advanced training. The guidelines are valid until the IGF-code entry into force, together with a new chapter in the STCW-convention. The advance training is required for personnel which are responsible for the use of fuel and fuel system, and the basic training is directed to other crew members. The training will together with a specialized fire training of LNG lead to certification. The result also shows that bunker procedure regarding LNG is the biggest change for the engine personnel and that the fire drills must be altered. Due to the use of LNG there is less soot forming in the combustion, thus are the maintenance interval longer and the use of cleaning agents decreases. Also, more time is given to conduct predictive maintenance. The conclusion states that changes in routines are not major and that ship-owners and universities are aware of the upcoming changes in the STCW-convention. Different methods are being examined in order to educate the engine room personnel in according with the demands of the future IGF-code.
Keywords: Annan teknik; Energi; Hållbar utveckling; Maskinteknik; Transport; Other Engineering and Technologies; Energy; Sustainable Development; Mechanical Engineering; Transport